An expedient and new synthesis of pyrrolo[1,2-b]pyridazine derivatives - Sagyam, Rajeshwar Reddy; Buchikonda, Ravinder; Pitta, Jaya Prakash; Vurimidi, Himabindu; Padi, Pratap Reddy; Ghanta, Mahesh Reddy (Beilstein Journal of Organic Chemistry, 2009)
The reaction of 2-[2-(4-fluorophenyl)-2-oxo-1-phenylethyl]-4-methyl-3-oxo-pentanoic acid phenylamide with tertiary butyl carbazate and subsequent condensation of the resulting carbamate derivative with a chalcone provided a facile new approach to pyrrolo[1,2-b]pyridazine derivatives.
Keywords: 1,4-diketone; migration and cyclization; pyrrolo[1,2-b]pyridazine; tertiary butyl carbamate; tertiary butyl carbazate; α,β-unsaturated ketone